Antimicrobial Activity Test of Ginseng bugis (talinum paniculatum gaertn.) Leaves Ethanol Extract against Pseudomonas aeruginosa, Propionibacterium Acnes, Streptococcus Mutans and Candida Albicans - Andi Emelda (Journal of Global Pharma Technology, 2020)
Ginseng bugis (Talinum panicullatum Gaertn.) leaf is traditionally used in the treatment of diarrhea, ulcers, wounds and skin infections by the people of South Sulawesi province. The leaves contain chemical compounds such as saponins, alkaloids, tannins, flavonoids and triterpenes which can be a source of antioxidants and bactericidal. This study aims to determine the antimicrobial activity of ginseng bugis leaf extract against the microbes. The test microbes used were Pseudomonas aeruginosa, Propionibacterium acnes, Streptococcus mutans, and Candida albicans which has been matured. The antimicrobial activity test used agar well diffusion method with ginseng bugis leaf extract solution with a concentration variation of 0.1%; 0.5%; 1%; 2%; 4%; 8%; 16%; and 32%. The inhibition zone observations were carried out on bacteria incubated at 37oC for 24 hours and fungi incubated at 25oC for 72 hours. The results of the inhibition zone measurement showed that the higher the concentration of the test solution for the ethanol extract of ginseng bugis leaves, the greater the inhibition zone given. Based on the results, the ethanol extract of ginseng bugis leaves had antimicrobial activity at the minimum inhibitory concentration of 1% against Pseudomonas aeruginosa, Propionibacterium acne, Candida albicans and a minimum inhibitory concentration of 4% against Streptococcus mutans. Keywords: Antimicrobial, Ethanol Extract, Talinum panicullatum Gaertn.